Rothia aeria and Rothia dentocariosa as biofilm builders in infective endocarditis - Dustin Greve; Annette Moter; Malte Christian Kleinschmidt; Frieder Pfäfflin; Miriam Songa Stegemann; Laura Kursawe; Herko Grubitzsch; Volkmar Falk; Judith Kikhney (Elsevier, 2021)
Background: Rothia sp. are Gram-positive bacteria in the class of Actinobacteria that are part of the physiological oral flora. In rare cases, Rothia aeria and Rothia dentocariosa can cause infective endocarditis (IE). The biofilm potential of Rothia in endocarditis is unknown. Methods: Specimen from two cases of Rothia endocarditis were obtained during cardiac surgery. One of the patients suffered mitral valve IE from Rothia aeria. In the other case, IE of a prosthetic pulmonary valve was caused by Rothia dentocariosa. Fluorescence in situ hybridization (FISH) was used for visualization of microorganisms within heart valve tissues in combination with PCR and sequencing (FISHseq). Results: The two heart valve specimens featured mature biofilms of bacteria that were identified by FISHseq as Rothia aeria and Rothia dentocariosa, respectively. FISH showed in situ biofilms of both microorganisms that feature distinct phenotypes for the first time ex vivo. Both of our reported cases were treated successfully by heart valve surgery and antibiotic therapy using beta-lactam antibiotics. Conclusion: The biofilm potential of Rothia sp. must be taken into account. The awareness of Rothia aeria and Rothia dentocariosa as rare but relevant pathogens for infective endocarditis must be raised. Use of biofilm-effective antibiotics in Rothia IE should be discussed.